Erratum: Analysis of production resources improvement strategies in make-to-stock environments managed by the simplified drum-buffer-rope system (Gestão & Produção (2021) 28:4 (e55) DOI: 10.1590/1806-9649-2021v28e55) - Govoni, Humberto [UNESP]; de Souza, Fernando Bernardi [UNESP]; Castro, Robson Flávio; de Souza Rodrigues, José [UNESP]; Ignacio Pires, Silvio Roberto (FapUNIFESP (SciELO), 2021)
Due to author's honest mistake the article “Analysis of production resources improvement strategies in make-to-stock environments managed by the simplified drum-buffer-rope system” (https://doi.org/10.1590/1806-9649-2021v28e55), published in Gestão & Produção, 28(4), e55, was published with errors. On page 27, where the text reads: Goldratt, E. M. (2009). Standing on the shoulders of giants: production concepts versus production applications: The Hitachi Tool Engineering example. Project Management Journal, 16(3), 333-343. It should read: Goldratt, E. M. (2009). Standing on the shoulders of giants: production concepts versus production applications: The Hitachi Tool Engineering example. Gestão & Produção, 16(3), 333-343. http://dx.doi.org/10.1590/S0104-530X2009000300002. On page 28, where the text reads: Pacheco, D. A. J., Lacerda, D. P., Corcini, S. L. H. No., Jung, C. F., & Antunes, J. A. V. Jr. (2014). Flow balancing or capacity balancing? Systemic analysis and propositions. Project Management Journal, 21(2), 355-367. Souza, F. B., & Baptista, H. R. (2010). Proposal of enhancement for the Simplified Drum-Buffer-Rope method applied to make-to-order production environments. Project Management Journal, 17(4), 735-746. Souza, F. B., & Pires, S. R. I. (1999). Analysis and propositions about the balancing and use of over capacity in productive resources. Project Management Journal, 6(2), 111-126. Souza, F. B., & Pires, S. R. I. (2014). Making to availability: an application of the Theory of Constraints in make-to-stock environments. Project Management Journal, 21(1), 65-76. Souza, F. B., Rentes, A. F., & Agostinho, L. O. (2002). The relationship between production planning and control systems and methods of capacity allocation. Project Management Journal, 9(2), 215-234. It should read: Pacheco, D. A. J., Lacerda, D. P., Corcini Neto, S. L. H., Jung, C. F., & Antunes Júnior, J. A. V. (2014). Balanceamento de fluxo ou balanceamento de capacidade? análises e proposições sistêmicas. Gestão & Produção, 21(2), 355-368. http://dx.doi.org/10.1590/S0104-530X2014005000006. Souza, F. B., & Baptista, H. R. (2010). Proposta de avanço para o método Tambor-Pulmão-Corda Simplificado aplicado em ambientes de produção sob encomenda. Gestão & Produção, 17(4), 735-746. http://dx.doi.org/10.1590/S0104-530X2010000400008. Souza, F. B., & Pires, S. R. I. (1999). Análise e proposições sobre o balanceamento e uso de excesso de capacidade em recursos produtivos. Gestão & Produção, 6(2), 111-126. http://dx.doi.org/10.1590/S0104-530X1999000200004. Souza, F. B., & Pires, S. R. I. (2014). Produzindo para disponibilidade: uma aplicação da Teoria das Restrições em ambientes de produção para estoque. Gestão & Produção, 21(1), 65-76. http://dx.doi.org/10.1590/S0104-530X2013005000007. Souza, F. B., Rentes, A. F., & Agostinho, O. L. (2002). A interdependência entre sistemas de controle de produção e critérios de alocação de capacidades. Gestão & Produção, 9(2), 215-234. http://dx.doi.org/10.1590/S0104-530X2002000200008. The authors apologize for the errors.